(untitled) (Journal of humanities and social sciences exploratio, 2025)
This paper presents a case study on the successful transformation of the high-quality television program Archaeological Notes into the bestselling book The Nanhai I Shipwreck,aiming to provide an in-depth analysis of how editorial expertise fosters new quality productive forces in the publishing industry within the context of media convergence.It argues that distinguished editors play a threefoldrole in cultivating new qualityproductive forces:as"gatekeepers""agenda-setters"and"converters of cultural capital"By systematically reviewing the entire project chain—from top-level design and content reshaping to integrated communication—this study elaborates on how an editor’s competence in resource integration,policy execution,and strategic planning drives a publishing project to achieve a win-win outcome in both social and economic benefits.Ultimately,it proposes a high-performance publishing model that leverages existing resources,capitalizes on the unique in-depth nature of books as a medium,and serves national cultural strategies,offering a valuable reference for product transformation,industrial upgrading,and talent development in China’s publishing industry.